Strategi Active Learning Tipe Everyone Is A Teacher Here (Eth) Berbasis Quiz terhadap Hasil Belajar - Elijonnahdi, Elijonnahdi; Suhaili, Hidayati; Sartini, Titi; Kartika, Wella (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this research is to find out the Active Learning Strategy of Everyone Is a Here (ETH) Type accompanied by Giving Quiz at the end of learning on the results of Biology class XII IA students. The research method uses experiments with the type of Quasi Experiment research intended to interpret the data from the research results. The population in the study were all class XII IA SMA N 1 Luhak Nan Duo, West Pasaman Regency, 139 students consisting of 4 classes. Sampling using purposive random sampling technique. The type of instrument used is a test in the form of objective questions. The results of the analysis stated that the t test (t-test) in the experimental class proved that the value of tcount was greater than ttable, namely = 1.71> 1.67), then Ha (alternative hypothesis) was accepted. Furthermore, the results of the t test (t-test) in the control class prove that the value proves that tcount is greater than t-table = 1.71> 1.67) then Ha (alternative hypothesis) is accepted. In conclusion, there is a significant influence in the use of Everyone Is a Here (ETH) Type Active Learning Strategy accompanied by Giving Quiz at the End of Learning on student learning outcomes. Keywords: Active Learning Strategy Everyone Is A Teacher Here (ETH) Type, Quez, Learning Outcomes